2022
DOI: 10.3389/fsufs.2022.987214
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of crops: Assessment of managerial flexibility and economic impact on sugarcane medium-sized farms

Abstract: The aim of this study is to assess the economic viability of a medium-sized sugarcane farm applying a diversification strategy, including the possibility of managerial flexibility in changing its portfolio over time. There is a theoretical gap in the economic evaluation of diversified production systems in farm space. We assessed one diversified structure for the sugarcane agricultural farm that included land areas dedicated to the rotational cultivation of soybean/corn, corn/peanut, and corn/green manure. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Adequate planting flexibility between both would tend to minimize risk and increase revenue. Furthermore, the results are also in line with those obtained by Santos and Gomes, 54 who found that the diversification and rotation of crops in the planting of sugarcane in the state of São Paulo, including soybeans and corn, also tends to maximize return and reduce the risks of individual investment projects.…”
Section: Data and Empirical Resultssupporting
confidence: 89%
“…Adequate planting flexibility between both would tend to minimize risk and increase revenue. Furthermore, the results are also in line with those obtained by Santos and Gomes, 54 who found that the diversification and rotation of crops in the planting of sugarcane in the state of São Paulo, including soybeans and corn, also tends to maximize return and reduce the risks of individual investment projects.…”
Section: Data and Empirical Resultssupporting
confidence: 89%
“…Farmers may show reluctance to this shift due to a lack of knowledge and expertise in modern techniques (Dorjee et al, 2003). Government support and guidance are crucial to successfully assist farmers through this transition as also mentioned in Fauzi et al, (2019);Felix & Ramappa, (2023) ;Ganguli, (2006);Indrawanto et al, (2021); Kurdyś-Kujawska, (2021); Mzyece et al, (2023); Santos & Gomes, (2022); Tashi & Wangchuk, (2016). The availability of skilled manpower and resources will encourage farmers to continue the large cardamom farming, which will in turn, will contribute to the nation's economic goals.…”
Section: Threatsmentioning
confidence: 99%